2017
DOI: 10.1159/000485287
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria-Targeted Antioxidant Mito-Tempo Protects Against Aldosterone-Induced Renal Injury In Vivo

Abstract: Background/Aims: Growing evidence suggests mitochondrial dysfunction (MtD) and the Nlrp3 inflammasome play critical roles in chronic kidney disease (CKD) progression. We previously reported that Aldosterone (Aldo)-induced renal injury in vitro is directly caused by mitochondrial reactive oxygen species (mtROS)-mediated activation of the Nlrp3 inflammasome. Here we aimed to determine whether a mitochondria-targeted antioxidant (Mito-Tempo) could prevent Aldo-induced kidney damage in vivo. Methods: C57BL/6J mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 32 publications
1
20
0
Order By: Relevance
“…Furthermore, it has been shown that NLRP3 can directly promote the TGF-β signal and activation of R-Smad independent of inflammasome (Wang et al, 2013), which offers new insights into the function and potential treatments of NLRP3 inflammasome in kidney disease. In addition, there are other potential treatment or drugs can reduce or inhibit tubular damage by interfering with the signal pathway of NLRP3 inflammasome; these include mitochondria target antioxidants, compound K, Neferine, allopurinol, and ghrelin (Ding et al, 2017;Foresto-Neto et al, 2018;Hsu et al, 2019;Ling et al, 2019).…”
Section: Inflammasomes In Chronic Kidney Diseasementioning
confidence: 99%
“…Furthermore, it has been shown that NLRP3 can directly promote the TGF-β signal and activation of R-Smad independent of inflammasome (Wang et al, 2013), which offers new insights into the function and potential treatments of NLRP3 inflammasome in kidney disease. In addition, there are other potential treatment or drugs can reduce or inhibit tubular damage by interfering with the signal pathway of NLRP3 inflammasome; these include mitochondria target antioxidants, compound K, Neferine, allopurinol, and ghrelin (Ding et al, 2017;Foresto-Neto et al, 2018;Hsu et al, 2019;Ling et al, 2019).…”
Section: Inflammasomes In Chronic Kidney Diseasementioning
confidence: 99%
“…ROS could be generated from different sources including mitochondria, ER stress, lysosomal dysfunction, and oxidases . Various ROS scavengers could inhibit ROS production through different manners as briefly shown in the figure .…”
Section: Treatment Of Antioxidants For Suppressing Nlrp3 Inflammasomementioning
confidence: 99%
“…It has been reported that mito‐T is a potent mitochondria‐targeted antioxidant, which could act in ischemic tissues linked with hypoxia‐induced oxidative stress (Ding, Liu, Bi, & Zhang, 2017; Du et al, 2019; Du, Farhood, & Jaeschke, 2017; Li et al, 2018; Liu, Wang, Ding, & Wang, 2018; Nautiyal, Shaltout, Chappell, & Diz, 2019; Shetty, Kumar, & Bharati, 2019; Yang et al, 2018; Zhan et al, 2018). In the present study, mito‐T, a mitochondria‐targeted superoxide dismutase mimetic, dramatically reduced AMA‐induced mitochondrial oxidative stress, and thus effectively protected MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that mito-T is a potent mitochondriatargeted antioxidant, which could act in ischemic tissues linked with hypoxia-induced oxidative stress (Ding, Liu, Bi, & Zhang, 2017;Du et al, 2019;Du, Farhood, & Jaeschke, 2017;Li et al, 2018;Liu, Wang, Ding, & Wang, 2018;Nautiyal, Shaltout, Chappell, & Diz, 2019;Shetty, Kumar, & Bharati, 2019;Yang et al, 2018;Zhan et al, 2018).…”
Section: Discussionmentioning
confidence: 99%